Pentahelix in the Development of Paloh Naga Agrotourism on the Socio-Economics of Village Communities from an Islamic Economic Perspective - Hasanah, Sri Nurul; Imsar, Imsar; Tambunan, Khairina (SENTRALISASI, 2024)
The aim of this research is to determine and analyze Pentahelix in the Development of Paloh Naga Agrotourism towards the Social Economy of Village Communities from an Islamic Economic Perspective. This research uses qualitative research which provides an actual, systematic and accurate picture of tourism development using the pentahelix model through descriptive methods. Tourism potential can develop rapidly if all stakeholders work together well, this is shown by the correlation between elements of the pentahelix model. Test the validity of the data using the triangulation method method. The results of this research are that Pentahelix in the development of Paloh Naga Agrotourism towards the Social Economy of the Denai Lama Tourism Village Community has been running optimally. In encouraging tourism progress, the role of various supporting parties is needed through creative ideas and innovation that work synergistically. Apart from that, the development of Agrotourism must always pay attention to the objectives of Islamic economics, namely that it must be in line and in accordance with Islamic law so that all ongoing tasks are directed towards the benefit of the people.